2003
DOI: 10.1080/0007131032000143573
|View full text |Cite
|
Sign up to set email alerts
|

Signs of change in Turkey's working class: workers' age-related perceptions in the modern manufacturing sector*

Abstract: This paper explores the possible effects of the increasing exposure to modernity on younger workers in some sectors of developing countries with special reference to those employed in advanced manufacturing in Turkey. In recent decades Turkey has undergone considerable urbanization, improvements in literacy and rising levels of formal education. The paper systematically examines differences in the work-related attitudes and expectations, commitment and aspirations of younger and older workers, who have been ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In this cross sectional study we lack the qualitative data that could cast further light on why this might be. However, a study of over 300 unionised [mostly men] workers in seven plants situated in or adjacent to the Izmit triangle, an area of extensive industrialisation which is home to many of the country's top companies, suggested that younger workers have higher expectations and aspirations that make them relatively less satisfied with a number of aspects of their work and which are likely to make for a less committed and more critical workforce (Nichols, Sugur and Tasiran 2003;Nichols and Sugur 2004: 185-200). It seems possible that this more highly developed sense of criticality among younger workers may extend to their relative lack of enthusiasm about joining the EU and that, in their eyes, EU membership may not represent the modernist/civilised future that some Europhiles outside Turkey would suppose.…”
Section: Discussionmentioning
confidence: 99%
“…In this cross sectional study we lack the qualitative data that could cast further light on why this might be. However, a study of over 300 unionised [mostly men] workers in seven plants situated in or adjacent to the Izmit triangle, an area of extensive industrialisation which is home to many of the country's top companies, suggested that younger workers have higher expectations and aspirations that make them relatively less satisfied with a number of aspects of their work and which are likely to make for a less committed and more critical workforce (Nichols, Sugur and Tasiran 2003;Nichols and Sugur 2004: 185-200). It seems possible that this more highly developed sense of criticality among younger workers may extend to their relative lack of enthusiasm about joining the EU and that, in their eyes, EU membership may not represent the modernist/civilised future that some Europhiles outside Turkey would suppose.…”
Section: Discussionmentioning
confidence: 99%